Implementation of a smoking cessation intervention for people with severe mental illness in ambulatory mental healthcare (KISMET): A process evaluation - Müge H. Küçükaksu; Lola Jansen; Trynke Hoekstra; Sanne Helmig; Marcel C. Adriaanse; Berno van Meijel (PLoS ONE, 2025)
Background Recently, a cluster-randomised controlled trial was conducted within Dutch ambulatory mental healthcare to assess the effectiveness of a one-year smoking cessation intervention consisting of group sessions, peer support and pharmacological treatment (KISMET). This article presents its process evaluation, exploring the perceptions of patients and mental healthcare professionals (MHPs) regarding the implementation of KISMET. Methods We conducted a mixed methods study, including 26 semi-structured interviews (10 MHPs and 16 patients) following the RE-AIM framework. Qualitative data was thematically analysed with MAXQDA software. We collected additional data on inclusion, drop-out and assessed treatment adherence during on-site observations. Results Recruitment and subsequent retention of patients in the RCT was found to be challenging (58% drop-out at one-year follow-up). MHPs suggested more motivational enhancement techniques to aid recruitment and reduce study attrition. The intervention components were generally assessed positively. Patients experienced the group and peer support sessions as supportive and beneficial. Inconsistent group attendance was demotivating and disrupted implementation. Pharmacological treatment was found to be helpful, although MHPs mentioned the treating psychiatrist or clinical nurse specialist need to facilitate better to ensure medication supply. The handbook offered MHPs excellent guidance and significantly contributed to treatment fidelity. Surprisingly, the carbon monoxide monitoring (originally included in the study protocol for research purposes) was appraised as a motivational tool. Finally, shortage of staff, limited collaboration and high turnover were barriers for the delivery of the intervention. Implementation heavily depends on the quality of the collaboration between MHPs and patients, as well as the infrastructure created by the organisation. Conclusion This study demonstrates the benefits, unique demands and challenges of a smoking cessation intervention for people with SMI. Results could guide and improve the implementation of smoking cessation interventions in mental healthcare settings. Fostering a culture of connectivity through team development, along with the provision of supportive and communicative supervision is critical for the effective recruitment and retention in smoking cessation studies in psychiatric care.